Úprava interních procesů vybraného podniku - Černohous, Šimon (Vysoké učení technické v Brně. Fakulta podnikatelská, 2025)
Diplomová práce se věnuje návrhem na úpravu procesů vybraného malého gastronomického podniku. Teoretická část vymezuje základní používané metodiky a přístupy, jako štíhlá výroba, procesní řízení, vybrané interní i externí analýzy a reflektuje specifika malých firem v kontextu jejich růstu. Analytická část nabízí podrobný pohled na vnitřní a vnější prostředí podniku, včetně získání dat důležitých pro další část práce. Návrhová část popisuje jednotlivé změny, ke kterým bylo přistoupeno.

The thesis focuses on designing process improvements for a selected small scale food service business. The theoretical part outlines key methodologies and approaches, including lean management, process management, and selected internal and external analyses and also it reflects on the specific characteristics of small enterprises in the context of their growth. The analytical part provides a detailed overview of the internal and external environment of the business, including data collection essential for further development. The proposal section presents specific changes that were implemented based on the findings.
Modification of internal processes of the selected company
Keywords: proces; malý podnik; method time measurement; rozvoj podniku; dotazníkové šetření; kaizen; TPS; řízení rizik; process; small business; method time measurement; business development; survey; kaizen; TPS; risk management